Simultaneous Determination of Five Minor Coumarins and Flavonoids in Glycyrrhiza uralensis by Solid-Phase Extraction and High-Performance Liquid Chromatography/Electrospray Ionization Tandem Mass Spectrometry - Qiao, Xue; Liu, Chun-Fang; Ji, Shuai; Lin, Xiong-Hao; Guo, De-An; Ye, Min (Planta Medica, 2014)
Minor phenolic compounds in licorice (Glycyrrhiza uralensis) have recently been proved for diverse bioactivities and favorable bioavailability, indicating that they may play an important role in the therapeutic effects or herb-drug interactions of licorice. However, so far, their abundance in licorice remains unknown. In this study, a reliable solid-phase extraction coupled with a high-performance liquid chromatography and diode array detection method was established to determine the minor phenolic compounds in licorice. The analytes were enriched by a three-step solid-phase extraction method, and then separated on a YMC ODS-A column by gradient elution. Five coumarins and flavonoids were identified by electrospray ionization tandem mass spectrometry, and then quantified using high-performance liquid chromatography and diode array detection. The amounts of glycycoumarin, dehydroglyasperin C, glycyrol, licoflavonol, and glycyrin in G. uralensis were 0.81 ± 0.28, 1.25 ± 0.59, 0.20 ± 0.08, 0.12 ± 0.04, and 0.17 ± 0.08 mg/g, respectively. Abundances of these compounds in other Glycyrrhiza species (G. glabra, G. inflata, and G. yunnanesis) were remarkably lower than G. uralensis.
Keywords: Glycyrrhiza uralensis; Leguminosae; licorice; SPE-HPLC-DAD; coumarins; flavonoids